Systematic Comparative Illustration of Primary School Building Regulations in Serbia and Slovenia - Sanja Stevanovic (European Scientific Journal, ESJ, 2017)
PISA tests provide international comparison of achieved educational standards through testing capabilities of 15-year old pupils. Serbia participates in PISA tests since 2003 and test reports show that the results of Serbian pupils are statistically significantly below the average of pupils in OECD countries. An additional concern, however, is the fact that the results of Serbian pupils are also statistically significantly below the results of Slovenian pupils. Slovenia participates in PISA tests since 2006 and the results of its pupils do not differ significantly from the OECD average. In order to discover directions for future reforms of educational system in Serbia in order to reach the OECD average, and therefore Slovenia, it is necessary to compare individual factors of educational systems in Serbia and Slovenia. Since pedagogical vision is of fundamental importance in design of schools, differences in primary school design regulations may serve to illustrate the most important differences in educational systems as well. A systematic comparative illustration of primary school design regulations in Serbia and Slovenia in this paper reveal that schools in Slovenia dedicate much more space, both quantitatively and qualitatively, to youngest pupils in preschool and the first two grades, school library and gym than their counterparts in Serbia.